Pendampingan LKPD Berbasis Genre Teks bagi Guru-Guru Bahasa Indonesia Sekolah Menengah Pertama sebagai Implementasi Kurikulum Merdeka: - - Mulyadi Eko Purnomo; Hani Atus Sholikhah; Didi Suhendi; Nandang Heryana; Riski Tamara (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
The community service to training in the preparation of text genre-based LKPD for junior high school Indonesian language subject teachers in Ogan Komering Ilir (OKI) Regency as an implementation of the Kurikulum Merdeka. Therefore, this activity was carried out so that junior high school teachers in OKI Regency could design LKPD properly. In addition, this activity is part of professional development activities for teachers. The methods used are material delivery, material simulation, mentoring, interaction, and assignments. material delivery, material simulation, and mentoring are intended to provide knowledge and insights with concrete examples related to text-based learning in the independent curriculum, types of text, and how to develop LKPD properly. An assignment is a practice activity of making LKPD exercises which are carried out individually then the results are discussed online through zoom. Each participant is asked to present their work and then be corrected together by peers and instructors. Based on the correction, the participants then revised the LKPD so that it became LKPD which was ready to be printed. At the beginning and end of the activity, a test was carried out in the form of self-reflection about knowledge of the LKPD.